Gambaran Pengawasan dan Implementasi Pengendalian Administratif Terhadap Insiden Pada Pekerjaan di Ketinggian di Proyek Konstruksi PT X - Iqbal Ata Dani (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The purpose of this thesis is to see an overview of supervision and implementation of administrative controls agains incidents at work at heights at construction project of PT X. Dependent variable for this thesis is incidence of work at heights, while  independent variable is administrative supervision and control. This research used descriptive qualitative using a case study design. In this research, researchers conduct field observations, in-depth interview and documents review that related to incidents of work at heights that have occurred. Data collection was carried out from July to August 2021. Data were analyzed in a qualitative descriptive through in-depth interviews using purposive sampling technique to the parties who signed work permit work at height starting from the foreman, safety officer, implementer (civil engineering person in the production division who is in the field), paramedic, construction manager and head of the Safety Health and Environment (SHE) division construction project of PT X. The result of this research showed neamiss incident that occurred in construction project of PT X. caused by lack of coordination beetween production team and SHE, SWA (Stop Work Authority) policy has not been maximally implemented, and inconsistent implementation of work permit. This phenomenon occured because the project almost finish and there are many targets that must be completed immediately.